Multicultural Education and the Reinforcement of Character Education: A Critical Review of Concepts, Theories, and Educational Approaches - Muhammad Ridwan; Mahyudin Ritonga; Julhadi Julhadi (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2026)
Social, cultural, religious, and ethnic diversity is an inseparable reality of Indonesian society. Within this context, education faces the challenge of not only producing learners who excel academically but also fostering individuals with tolerant, just, and civilized character. Multicultural education is regarded as a strategic and relevant approach to strengthening character education, as it positions respect for diversity as an integral component of the learning process. Nevertheless, comprehensive theoretical studies that systematically examine the conceptual, theoretical, and methodological relationships between multicultural education and character education remain limited and require further exploration. This study aims to examine and analyze the concepts, theoretical foundations, and approaches of multicultural education in relation to the strengthening of character education. This research employs a qualitative approach in the form of library research. Data were obtained from various scholarly sources, including textbooks, national and international journal articles, conference proceedings, and relevant educational policy documents. Data analysis was conducted using content analysis techniques through the stages of data reduction, data presentation, and conclusion drawing, and was further strengthened through source triangulation to ensure data validity. The findings indicate that multicultural education plays a fundamental role in strengthening character education, particularly in cultivating values such as tolerance, empathy, justice, responsibility, and mutual respect. Theoretically, multicultural education and character education are complementary and cannot be separated from the social and cultural contexts in which learners live and interact. The implementation of multicultural education through inclusive, dialogical, and equitable learning approaches has been shown to create a conducive educational environment for character development. The integration of multicultural education and character education thus constitutes a strategic approach to developing a generation with strong character, social awareness, and the capacity to live harmoniously within a multicultural society.